2019
DOI: 10.1111/jon.12628
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Basal Ganglia Using Diffusion Tensor Imaging in Children with Self‐Injurious Behavior and Tuberous Sclerosis Complex

Abstract: BACKGROUND AND PURPOSE Tuberous sclerosis complex (TSC) is a rare, genetic disease that is associated with multiple manifestations including epilepsy and autism. Self‐injurious behaviors (SIBs) also occur in a subset of patients. This study used diffusion tensor imaging (DTI) in children with TSC for quantitative and volumetric analysis of brain regions that have been associated with SIB in other genetic conditions. METHODS We used DTI to compare 6 children with TSC‐associated SIB and 10 children with TSC with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…However, whether this association is due to the severe epilepsy caused by a high tuber load or due to the tuber load itself remains unclear. According to Gipson et al, patients with self-injurious behavior-associated TSC have higher frequencies of tubers in quadrants other than the left posterior neuroanatomical region (15). We found that tuber load and its localization correlate with certain neuropsychiatric symptoms.…”
Section: Discussionsupporting
confidence: 57%
“…However, whether this association is due to the severe epilepsy caused by a high tuber load or due to the tuber load itself remains unclear. According to Gipson et al, patients with self-injurious behavior-associated TSC have higher frequencies of tubers in quadrants other than the left posterior neuroanatomical region (15). We found that tuber load and its localization correlate with certain neuropsychiatric symptoms.…”
Section: Discussionsupporting
confidence: 57%
“…(46,52,98). Hence, a number of studies have attempted to use DTI to investigate the anatomical alterations in white and gray matter structures that underlie the neurocognitive morbidity in TSC patients (6,41,66,80). The absence of brain malformations such as tubers in the heterozygous mouse models of Tsc1 +/− and Tsc2 +/− , which both show poor learning and memory performance and social behavior, also suggest that other subtle microscopic structural changes may account for neurologic symptoms (36,87).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, this altered striatal activity was correlated with the presence of RRBs in the TSC children with ASD (Asano et al, 2001). Recently, the presence of self-injurious behavior in individuals with TSC was shown to be associated with structural changes in basal ganglia nuclei (Gipson et al, 2019).…”
Section: Introductionmentioning
confidence: 99%